A educação linguística, o professor e o livro didático: desenvolvimento da pedagogia da leitura - Bertoletti, Márcia Lenise (2016)
The present research, placed in the research line Reading, writing and teaching of Portuguese Language of Portuguese Language Studies Programme, has its theme focused on the relationship between Linguistic Education, teacher and textbook in the 9th grade of elementary school from public schools, in reference of knowledge building and the reading comprehension by ApEn, in the light of Linguistic Education. The questions that orientated this research were 1 "How Linguistic Education, teacher and textbook make possible to the ApEn the building of his knowledge in relation to the traditional teaching model?", 2 "What way Linguistic Education favor the teacher, or EnAp, to stop being a knowledge transmission to be an advisor, who aids ApEn to build his own knowledge?", 3 "The teacher, or EnAp, understands the concept of Linguistic Education to be able to transfer it to the pedagogical reading activities?", and 4 "The new role of EnAp is motivated in the textbook?". Its goals are to identify the building of knowledge and the reading comprehension by ApEn through the relationship between Linguistic Education, teacher and textbook; to investigate which will be the strategies to enable EnAp to let being a person that just transmit knowledge to be a mediator in the teaching-learning process; to identify in the textbooks the opportunities and strategies offered to the AnEn, in a active role, reaches the reading comprehension; to identify how the transposition of Linguistic Education is done by EnAp to ApEn in the practice of classroom; to investigate how the Linguistic Education is merged or not in the textbooks; to identify if the EnAp is stimulated through textbook to act in an autonomous way. A review of the literature was performed based upon data from Linguistic Education theoretician (PALMA and TURAZZA (2014), LOMAS (2003), FIGUEIREDO (2010)), Reading and Reading Pedagogy (KLEIMAN (2013), SOLÉ (2009) e FIGUEIREDO (2010)), and Active Methodologies (MOSATTO (2016)). As part of the analyzed material, it was applied 06 questionnaires, being the respondents 9th grade teachers in elementary school from public schools, and the analysis of the reading activities from a Portuguese Language textbook for 9th grade. 8 The results showed that the Linguistic Education, through the work with active methodologies and textual genre, stimulates the EnAp to assume his new role as a mediator, giving voice to ApEn. The textbooks need to follow this change making available more room to ApEn autonomy during this practice in the classroom. The reading activities suggested in the textbook must be more aligned to the Linguistic Education to enable ApEn to build his own knowledge